Dimethyl fumarate: a novel drug for multiple sclerosis - Singh, Jatinder; Mahajan, Bharti; Kaushal, Sandeep (International Journal of Basic & Clinical Pharmacology, 2017)
Dimethyl fumarate (DMF) is a novel oral immunomodulatory and neuroprotective drug that was approved by FDA for relapsing forms of multiple sclerosis (MS). The initial use of DMF was for the treatment of psoriasis where its long-term use was safe and efficacious, and it also got German approval for the same. It was found that the anti-inflammatory actions of DMF contributed to its efficacy in psoriasis. This anti-inflammatory action of DMF created interest using DMF in other auto-immune or inflammatory diseases, including MS. DMF acts by decreasing production and release of inflammatory molecules. DMF also activates the nuclear factor-erythroid 2 related factor pathway which induces the transcription of various genes, including anti-oxidative ones, reduces oxidative neuronal death and helps maintain myelin integrity. Thus, DMF acts via two pathways: by down-regulating oxidative stress and corresponding cellular injury, as well as by inhibiting pro-inflammatory cytokines. DMF is an orally administered, enteric-coated microtablet preparation. There was a 44-53% reduction in annualized relapse rate with the use of DMF in patients with relapsing form of MS. The most common adverse reactions reported are flushing, abdominal pain, diarrhea, and nausea, which are more prominent during initial treatment and usually decrease over time. No serious adverse events were seen during the phase II and III trials, including no increased risk of opportunistic infections or cancer. DMF seems to approach the ideal combination of safety, efficacy and well-tolerability to other approved oral therapies for MS.